Students' Capability In Writing Descriptive Text At The Eighth Grade Of SMP 1 Muhammadiyah Surakarta In 2014/2015 Academic Year - Baskoro, Arief, Aryati Prasetyarini, S.Pd, M.Pd, Siti Fatimah, S. Pd, M. Hum (2015)
This research aims to describe the students' capability writing descriptive text, to identify the problem faced by the students in writing descriptive text and to identify the cause of the problem faced by the students in writing descriptive text at the eighth grade of SMP Muhammadiyah 1 Surakarta in 2014/2015 academic year. The method of collecting data is interview and analyzing document. The technique of data analysis is to answer the students' capability in writing descriptive. The researcher analyzed the students' writing based on (a) content of the composition, (b) organization of the paragraph, (c) Grammar, (d) Vocabulary, and (e) mechanic. There is no text is categorized in excellence grade. There are 6 students or 21, 4%. There are 16 students or 57, 1%. There are 6 students or 21, 4%. The problem faced by the students in writing are (1) the students have problems with the lack of vocabulary, (2) the students feel difficult to express and develop idea in descriptive text, (3) The students have problem with the low mastery of grammar. The causes of problem faced are (1) students are not interested in English language, (2) convey the descriptive text from the teacher, (3) Background knowledge vocabulary.